Preparation method and application of aerogel microspheres for separating panax notoginseng saponins

Modified montmorillonite-nanocellulose composite aerogel microspheres were prepared by acidification and organic modification of montmorillonite, combined with calcium cross-linking and freeze-drying technology, and solved the environmental pollution of the separation and purification of total saponin in the prior art in the existing technology The problem of insufficient research on biomass adsorbents has achieved green and environmentally friendly and efficient separation and purification effect.

CN119258994APending Publication Date: 2025-01-07GUANGXI UNIV FOR NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411345842.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, the separation and purification method of Panax notoginseng total saponin has problems such as environmental pollution and less research on biomass adsorbents, especially macroporous resins are non-renewable resources, and insufficient research on biomass adsorbents makes it difficult to achieve green environmental protection. Isolate and purify.

Method used

Modified montmorillonite-nanocellulose composite aerogel microspheres were prepared by acidification and organic modification of montmorillonite, combined with calcium cross-linking and freeze-drying technology, and used for the separation and purification of panax notoginseng saponins. Specific steps include stirring sodium alginate solution and modified montmorillonite in nanocellulose solution, and freeze-dried after calcium cross-linking to prepare aerogel microspheres.

Benefits of technology

The green and environmentally friendly separation and purification of Panax notoginseng total saponin was achieved, and a new adsorbent was provided, which simplified the preparation process and improved the adsorption effect. It also showed that the proportion of composite aerogel microspheres in CTAB modified montmorillonite K10 was 40%. The best adsorption effect is under the conditions of 4% OMA ratio, 2% SA ratio, 7 pH, adsorption time of 16h and adsorption temperature of 35°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258994A_ABST
    Figure CN119258994A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of aerogel microspheres for separating panax notoginseng saponins, and the preparation method comprises the following steps: acidifying montmorillonite K10 with hydrochloric acid, modifying montmorillonite with an organic surfactant hexadecyl trimethyl ammonium bromide, adding a sodium alginate solution into a nano-cellulose suspension, and stirring uniformly to obtain the aerogel microspheres for separating panax notoginseng saponins. The preparation method comprises the following steps: adding nano cellulose into a CaCl2 solution, adding the nano cellulose into modified montmorillonite, uniformly stirring to obtain a mixed solution, slowly dropwise adding the mixed solution into the CaCl2 solution by using an injector, carrying out calcium crosslinking to obtain composite gel microspheres, and freeze-drying to obtain the modified montmorillonite-nano cellulose composite aerogel microspheres. Montmorillonite has the advantages of large specific surface area, low price, good adsorption capacity and the like; the nano cellulose has the characteristics of high specific surface area, environment friendliness, reproducibility and the like, the cellulose aerogel is widely applied to the field of adsorption as a porous material, and the green and environment-friendly biomass adsorbent is prepared by combining the characteristics of the two materials and has important significance in separation and purification of panax notoginseng saponins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation and purification of notoginseng total saponins, and particularly relates to a preparation method and application of aerogel microspheres for separating notoginseng total saponins. Background Art

[0002] Panax notoginseng (Burk.) FH Chen, also known as mountain lacquer, is the root of Panax notoginseng, a plant of the genus Panax in the Araliaceae family. It is a Chinese herbal medicine that has the effects of promoting blood circulation and relieving pain. It has extremely high medicinal value and is mainly distributed in Yunnan, Guangxi and other regions. Panax notoginseng contains a variety of chemical components such as saponins, flavonoids, cyclic peptides, sugars and amino acids, and the main active ingredient is saponin compounds. There are many types of saponins, all of which are dammar-type tetracyclic triterpenoid compounds, which have the effects of protecting nerves, protecting cardiovascular and immune systems, anti-inflammatory, anti-depressant, anti-atherosclerosis and anti-tumor. The main components of saponins are Panax notoginseng saponins (PNS), Panax notoginseng saponins R1 and ginsenosides Rg1, Re, Rb1, Rd, which account for about 90% of Panax notoginseng saponins. Currently, Panax notoginseng total saponins are widely used in clinical practice and have broad application prospects. However, due to the complexity of the effective ingredients of Panax notoginseng, the separation and purification of Panax notoginseng total saponins are challenging. Adsorption is a widely used separation and purification method. Currently, there is little research on biomass adsorbents. It is of great significance to synthesize green and environmentally friendly adsorption materials for the separation and purification of Panax notoginseng total saponins.

[0003] Biomass-based adsorbents have the advantages of being renewable, biodegradable and environmentally friendly. Montmorillonite is a clay mineral with a layered nanostructure that has the advantages of being cheap, having a large specific surface area and being naturally available. Nanocellulose has excellent mechanical properties, good biocompatibility and is green and renewable. Cellulose aerogel, as a porous material, is widely used in the field of adsorption. Combining the characteristics of the two materials, green and environmentally friendly composite aerogel microspheres are prepared and applied to the separation and purification of Panax notoginseng total saponins. Summary of the invention

[0004] At present, macroporous resin is mainly used to separate and purify Panax notoginseng total saponins. The commonly used resin is styrene resin, which uses petrochemicals as raw materials. It is a non-renewable resource and will cause environmental pollution. In addition, there is little research on the adsorption of Panax notoginseng total saponins by biomass adsorbents. Therefore, biomass materials are used to synthesize green and environmentally friendly adsorbents for the separation and purification of Panax notoginseng total saponins.

[0005] The specific technical scheme of the present invention is: a preparation method for separating notoginseng total saponin aerogel microspheres, characterized in that montmorillonite is firstly acidified and organically modified, and then modified montmorillonite-nanocellulose composite aerogel microspheres are prepared by calcium crosslinking and freeze-drying technology.

[0006] Follow the steps below to implement it:

[0007] (a) adding sodium alginate into an aqueous solution and heating to dissolve the sodium alginate solution;

[0008] (b) adding the sodium alginate solution and the modified montmorillonite into the nanocellulose solution, stirring and dispersing them uniformly to obtain a mixed solution;

[0009] (c) using a syringe to drop the mixed solution into a CaCl2 solution to obtain gel microspheres through calcium cross-linking;

[0010] (d) Aerogel microspheres were obtained by freeze drying.

[0011] Furthermore, in step (a), the ratio of sodium alginate solution is 1-4%, the heating and dissolving temperature is 65° C., and the stirring time is 1 hour.

[0012] Furthermore, in step (b), the mass ratio of the sodium alginate solution to the nanocellulose is 1:1, and the proportion of the modified montmorillonite is 1% to 5% of the total mass.

[0013] Furthermore, in step (c), the syringe range is 5 mL and 10 mL respectively, and the calcium cross-linking time is 24 h.

[0014] Furthermore, in step (b), the modified montmorillonite is montmorillonite K10 that has been acidified and organically modified.

[0015] Another object of the present invention is to apply the composite aerogel microspheres prepared by the above method to the separation and purification of Panax notoginseng total saponins.

[0016] The beneficial effects of the present invention are:

[0017] 1. Modified montmorillonite-nanocellulose composite aerogel microspheres were prepared by calcium cross-linking and freeze-drying technology for the adsorption of Panax notoginseng total saponins. Currently, there are few studies on the adsorption of Panax notoginseng total saponins by green and environmentally friendly biomass adsorbents. The preparation method of CMSA is simple, green and environmentally friendly, and the raw material sources are wide. It provides new ideas for the development of new adsorbents to separate and purify Panax notoginseng total saponins.

[0018] 2. The aerogel microspheres prepared by the present invention have the best adsorption effect on Panax notoginseng total saponins under the conditions of CTAB modified montmorillonite K10 ratio of 40%, OMA ratio of 4%, SA ratio of 2%, addition amount of 0.25g, pH of 7, adsorption time of 16h, and adsorption temperature of 35°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Flow chart for the preparation of CMSA

[0020] Figure 2 Infrared spectra of MK, MA, OMA and CMSA

[0021] Figure 3 Thermal stability curves of MK, MA, OMA and CMSA

[0022] Figure 4 XRD patterns of MK, MA, OMA and CMSA

[0023] Figure 5 Optimization of conditions for CMSA preparation

[0024] Figure 6 To study the adsorption performance of CMSA by single factor

[0025] Figure 7 Analysis of the adsorption performance of OMA, CSA and CMSA on PNS

[0026] Figure 8 Exploration of elution conditions for CMSA

[0027] Fig. 9 Repeatability performance for CMSA

[0028] Fig.10 Liquid chromatography spectra of crude Panax notoginseng liquid before and after CMSA purification DETAILED DESCRIPTION

[0029] The specific implementation method of the present invention is described in detail below in conjunction with the embodiments.

[0030] Example 1

[0031] A method for preparing composite aerogel microspheres for separating notoginseng total saponins comprises the following steps:

[0032] (a) Acid modification of montmorillonite

[0033] Take 20g MK and add it to a conical flask, add 600mL hydrochloric acid (2%, v:v) solution, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, the speed is 220r / min, let it stand to room temperature after acidification, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with deionized water and repeat the above process until there is no precipitation when AgNO3 is added, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve to obtain MA.

[0034] (b) Organic modification of montmorillonite

[0035] Take 10g MA and 2g CTAB and add them into a conical flask, add deionized water, seal it and place it in an oil bath, stir it mechanically at 65℃ for 24h, the stirring speed is 220r / min, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with ethanol and deionized water respectively, centrifuge it, repeat the operation three times, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve it to obtain OMA.

[0036] (c) Preparation of CMSA

[0037] 1% sodium alginate (m:m) was added to the nanocellulose suspension, and 1% OMA (m:m) was added and stirred evenly to obtain a mixed solution, which was loaded into a 10 mL syringe and slowly added dropwise to the CaCl2 solution. Gel microspheres were obtained by calcium cross-linking, and freeze-dried to obtain montmorillonite and nanocellulose composite aerogel microspheres.

[0038] Example 2

[0039] A method for preparing composite aerogel microspheres for separating notoginseng total saponins comprises the following steps:

[0040] Acid modification of montmorillonite

[0041] Take 20g MK and add it to a conical flask, add 600mL hydrochloric acid (2%, v:v) solution, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, the speed is 220r / min, let it stand to room temperature after acidification, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with deionized water and repeat the above process until there is no precipitation when AgNO3 is added, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve to obtain MA.

[0042] (b) Organic modification of montmorillonite

[0043] Take 10g MA and 4g CTAB and add them into a conical flask, add deionized water, seal it and place it in an oil bath, stir it mechanically at 65℃ for 24h, the stirring speed is 220r / min, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with ethanol and deionized water respectively, centrifuge it, repeat the operation three times, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve it to obtain OMA.

[0044] (c) Preparation of CMSA

[0045] 2% sodium alginate (m:m) was added to the nanocellulose suspension, and 2% OMA (m:m) was added and stirred evenly to obtain a mixed solution, which was loaded into a 5 mL syringe and slowly added dropwise to the CaCl2 solution. Gel microspheres were obtained by calcium cross-linking, and freeze-dried to obtain montmorillonite and nanocellulose composite aerogel microspheres.

[0046] Example 3

[0047] A method for preparing composite aerogel microspheres for separating notoginseng total saponins comprises the following steps:

[0048] (a) Acid modification of montmorillonite

[0049] Take 20g MK and add it to a conical flask, add 600mL hydrochloric acid (2%, v:v) solution, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, the speed is 220r / min, let it stand to room temperature after acidification, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with deionized water and repeat the above process until there is no precipitation when AgNO3 is added, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve to obtain MA.

[0050] (b) Organic modification of montmorillonite

[0051] Take 10g MA and 6g CTAB and add them into a conical flask, add deionized water, seal it and place it in an oil bath, stir it mechanically at 65℃ for 24h, the stirring speed is 220r / min, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with ethanol and deionized water respectively, centrifuge it, repeat the operation three times, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve it to obtain OMA.

[0052] (c) Preparation of CMSA

[0053] 3% sodium alginate (m:m) was added to the nanocellulose suspension, and 3% OMA (m:m) was added and stirred evenly to obtain a mixed solution, which was loaded into a 5 mL syringe and slowly added dropwise to the CaCl2 solution. Gel microspheres were obtained by calcium cross-linking, and freeze-dried to obtain montmorillonite and nanocellulose composite aerogel microspheres.

[0054] Example 4

[0055] A method for preparing composite aerogel microspheres for separating notoginseng total saponins comprises the following steps:

[0056] (a) Acid modification of montmorillonite

[0057] Take 20g MK and add it to a conical flask, add 600mL hydrochloric acid (2%, v:v) solution, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, the speed is 220r / min, let it stand to room temperature after acidification, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with deionized water and repeat the above process until there is no precipitation when AgNO3 is added, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve to obtain MA.

[0058] (b) Organic modification on montmorillonite

[0059] Take 10g MA and 8g CTAB and add them into a conical flask, add deionized water, seal it and place it in an oil bath, stir it mechanically at 65℃ for 24h, the stirring speed is 220r / r / min, centrifuge it at 4000r / r / min for 10 min, discard the supernatant, wash it with ethanol and deionized water respectively, centrifuge it, repeat the operation three times, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve it to obtain OMA.

[0060] (c) Preparation of CMSA

[0061] 4% sodium alginate (m:m) was added to the nanocellulose suspension, and 4% OMA (m:m) was added and stirred evenly to obtain a mixed solution, which was loaded into a 5 mL syringe and slowly added dropwise to the CaCl2 solution. Gel microspheres were obtained by calcium cross-linking, and freeze-dried to obtain montmorillonite and nanocellulose composite aerogel microspheres.

[0062] Example 5

[0063] A method for preparing composite aerogel microspheres for separating notoginseng total saponins comprises the following steps:

[0064] (a) Acid modification of montmorillonite

[0065] Take 20g MK and add it to a conical flask, add 600mL hydrochloric acid (2%, v:v) solution, seal it and place it in an oil bath, stir it mechanically at 50℃ for 5h, the speed is 220r / min, let it stand to room temperature after acidification, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with deionized water and repeat the above process until there is no precipitation when AgNO3 is added, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve to obtain MA.

[0066] (b) Organic modification of montmorillonite

[0067] Take 10g MA and 10g CTAB and add them into a conical flask, add deionized water, seal it and place it in an oil bath, stir it mechanically at 65℃ for 24h, the stirring speed is 220r / min, centrifuge it at 4000r / min for 10min, discard the supernatant, wash it with ethanol and deionized water respectively, centrifuge it, repeat the operation three times, place it in a vacuum drying oven, dry it at 60℃ for 24h, grind and sieve it to obtain OMA.

[0068] (c) Preparation of CMSA

[0069] 2% sodium alginate (m:m) was added to the nanocellulose suspension, and 5% OMA (m:m) was added and stirred evenly to obtain a mixed solution, which was loaded into a 5 mL syringe and slowly added dropwise to the CaCl2 solution. Gel microspheres were obtained by calcium cross-linking, and freeze-dried to obtain montmorillonite and nanocellulose composite aerogel microspheres.

[0070] In order to prove the adsorption effect of the present invention, the inventor conducted a scientific experiment. The specific experimental process and data are as follows:

[0071] Experiment 1

[0072] Effect of CTAB modification ratio on adsorption performance:

[0073] The proportion of CTAB-modified montmorillonite was set to 20-100% (m / m), and the corresponding aerogel microspheres were named A CMSA (A represents the proportion of CTAB modification); 0.2 g A CMSA and 10 mL of 4 mg / mL Panax notoginseng total saponin solution were added to a 25 mL conical flask, placed on a shaker, and oscillated at 150 r / min at room temperature for 24 h. The supernatant was taken and passed through a 0.22 μm aqueous membrane. The solution concentration was measured by liquid phase, and the adsorption amount and adsorption rate were calculated.

[0074] Experiment 2

[0075] Effect of SA ratio on adsorption performance:

[0076] The SA content was set to 1-4% (m / m), and the corresponding aerogel microspheres were named B-CMSA (B represents the SA ratio); 0.2 g B-CMSA and 10 mL of 4 mg / mL Panax notoginseng total saponin solution were added to a 25 mL conical flask, placed on a shaker, and oscillated at 150 rpm at room temperature for 24 h. The supernatant was taken and passed through a 0.22 μm aqueous membrane. The solution concentration was measured by liquid phase, and the adsorption amount and adsorption rate were calculated.

[0077] Experiment 3

[0078] Effect of OMA ratio on adsorption performance:

[0079] The OMA content was set to 1-5% (m / m) of the total mass, and the corresponding aerogel microspheres were named CMSA-C (C represents the OMA ratio); 0.2 g CMSA-C and 10 mL of 4 mg / mL Panax notoginseng total saponin solution were added to a 25 mL conical flask, placed on a shaker, and oscillated at 150 rpm at room temperature for 24 h. The supernatant was taken and passed through a 0.22 μm aqueous membrane. The solution concentration was measured by liquid phase, and the adsorption amount and adsorption rate were calculated.

[0080] Experiment 4

[0081] Effect of CMSA size on adsorption performance:

[0082] Aerogel microspheres were prepared using 5mL and 10mL syringes, and the corresponding aerogel microspheres were named CMSAD (D corresponds to the syringe range); 0.2g CMSA D and 10mL of 4mg / mL Panax notoginseng total saponin solution were added to a 25mL conical flask, placed on a shaker, and shaken at room temperature at 150r / min for 24h. The supernatant was taken and passed through a 0.22μm aqueous membrane. The solution concentration was measured by liquid phase, and the adsorption amount and adsorption rate were calculated.

[0083] Experiment 5

[0084] Effect of dosage on CMSA adsorption performance:

[0085] Take 10mL of 5mg / mL Panax notoginseng total saponin solution and add it into a 25mL conical flask, add 0.1-0.5g CMSA respectively, place it on a shaker, oscillate at room temperature at 150r / min for 24h, take the supernatant, pass it through a 0.22μm aqueous membrane, measure the solution concentration by liquid phase, and calculate the adsorption amount and adsorption rate.

[0086] Experiment 6

[0087] Effect of adsorption temperature on the adsorption performance of CMSA:

[0088] Add 0.25 g CMSA and 10 mL of 5 mg / mL Panax notoginseng total saponin solution into a 25 mL conical flask, place it on a shaker, oscillate at 150 r / min, and at 15-45 °C for 24 h. Take the supernatant, pass it through a 0.22 μm aqueous membrane, measure the solution concentration by liquid phase, and calculate the adsorption amount and adsorption rate.

[0089] Experiment 7

[0090] Effect of adsorption pH on the adsorption performance of CMSA:

[0091] Prepare 0.1M NaOH and 0.1M HCl solutions, adjust the pH to 3-11 respectively, prepare 5 mg / mL Panax notoginseng total saponin solution, add 10mL Panax notoginseng total saponin solution of different pH values ​​into a conical flask, add 0.25g CMSA and place on a shaker, shake at 150r / min at room temperature for 24h, take the supernatant, pass it through a 0.22μm aqueous membrane, measure the solution concentration by liquid phase, and calculate the adsorption amount and adsorption rate.

[0092] Experiment 8

[0093] Effect of adsorption time on the adsorption performance of CMSA:

[0094] Take 100 mL of 5 mg / mL Panax notoginseng total saponins and add it into a 150 mL conical flask, add 2.5 g CMSA, rotate at 150 r / min, oscillate at room temperature, take samples every 1 h, pass through a 0.22 μm aqueous membrane, measure the solution concentration before and after adsorption by liquid phase, and calculate the adsorption amount.

[0095] A series of characterizations including FTIR, thermogravimetric analysis, and XRD analysis of composite aerogel microspheres.

[0096] Result analysis:

[0097] Figure 1 Flow chart for CMSA preparation.

[0098] like Figure 2 As shown, OMA and CMSA are at 2846 and 2920 cm -1 There are antisymmetric stretching peaks and symmetric stretching peaks of CH2 at 1472cm -1 The angular vibration occurs because CTAB carries a long-chain alkyl group, which indicates that CTAB has successfully modified montmorillonite and CMSA has been successfully prepared.

[0099] like Figure 3 a and 3b show that there are three stages of thermal decomposition of montmorillonite. In the first stage, the mass decreases slightly in the range of 40-130 °C, and the residual water in the sample evaporates; in the second stage, the mass loss is more significant in the range of 180-330 °C, mainly due to the escape of crystal water inside the montmorillonite; in the third stage, the mass decreases slightly in the range of 380-480 °C, and the montmorillonite undergoes thermal decomposition; Figure 3 As shown in Fig. 3, there are four stages in the thermal decomposition of composite aerogel microspheres. In the first stage, the mass begins to lose in the range of 40-208 °C, and the crystalline water inside the montmorillonite escapes. In the second stage, the mass decreases significantly in the range of 208-343 °C, due to the initial thermal decomposition of the main structural substances SA and CNF. In the third stage, CNF and SA undergo further thermal decomposition in the range of 343-451 °C. In the fourth stage, the mass decreases slightly in the range of 451-546 °C, and the montmorillonite undergoes thermal decomposition.

[0100] like Figure 4 As shown, the diffraction curve of montmorillonite is a characteristic reflection of the layered structure (001) at 20 (5.82). It is observed that the (001) of acid-modified montmorillonite is slightly shifted to the left, and the peak intensity is weakened. The interplanar spacing is CTAB modified montmorillonite. CTAB was inserted into the interlayer of montmorillonite. The characteristic peak corresponding to the (001) plane shifted to the left, and the interplanar spacing of OMT increased significantly. CMSA has the diffraction peaks unique to montmorillonite, indicating that the aerogel microspheres were successfully prepared.

[0101] like Figure 5 As shown, the CTAB modification ratio was 40%, the SA ratio was 2%, the OMA ratio was 4%, and the syringe range was 5 mL to prepare CMSA.

[0102] like Figure 6As shown, the best adsorption effect of Panax notoginseng total saponins was achieved when the dosage was 0.25 g, the adsorption temperature was 35°C, the pH was 7, and the adsorption time was 16 h.

[0103] like Figure 7 As shown, the adsorption performance of CMSA is better than that of aerogel microspheres (CSA) without modified montmorillonite and OMA.

[0104] like Figure 8 As shown, a 60% ethanol solution was selected as the eluent.

[0105] like Fig. 9 As shown, CMSA was adsorbed 5 times repeatedly, and the adsorption rate was still above 80%, which has good repeatability.

[0106] like Fig.10 As shown, the purity of the crude extract of Panax notoginseng was improved from 33.15% to 79.26% by CMSA purification.

[0107] The above embodiments describe the present invention in detail. These embodiments are only used to illustrate the present invention and do not limit the protection scope of the present invention.

Claims

1. A method for preparing aerogel microspheres for separating notoginseng total saponins, characterized in that: The preparation method includes the following: (1) adding sodium alginate into an aqueous solution and heating to dissolve the sodium alginate solution; (2) adding the sodium alginate solution to the nanocellulose solution and stirring evenly to obtain a mixed solution; (3) using a syringe to drop the mixed solution into a CaCl2 solution, and calcium cross-linking is performed to obtain gel microspheres; (4) Freeze-drying to obtain aerogel microspheres.

2. A method for preparing aerogel microspheres for separating notoginseng total saponins as claimed in claim 1, the preparation method comprising the following steps: (1) adding sodium alginate into an aqueous solution and heating to dissolve the sodium alginate solution; (2) adding the sodium alginate solution and the modified montmorillonite into the nanocellulose solution, stirring evenly to obtain a mixed solution; (3) using a syringe to drop the mixed solution into a CaCl2 solution, and calcium cross-linking is performed to obtain gel microspheres; (4) Freeze-drying to obtain aerogel microspheres.

3. A method for preparing aerogel microspheres for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: The ratio of sodium alginate is 1% to 4%.

4. A method for preparing aerogel microspheres for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: The mass of modified montmorillonite is 1% to 5% of the total mass.

5. A method for preparing aerogel microspheres for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: The syringe volume is 5mL or 10mL.

6. A method for preparing aerogel microspheres for separating notoginseng total saponins as claimed in claim 1 or 2, characterized in that: Freeze for 24 hours and freeze-dry for 48 hours.

7. Aerogel microspheres for separating Panax notoginseng total saponins, prepared by the method according to any one of claims 1 to 6.

8. Use of the composite aerogel microspheres as claimed in claim 7 for separation and purification of notoginseng total saponins in Panax notoginseng.